A spatiodynamic model for assessing frost risk in south‐eastern Australia. Issue 5 (29th April 2015) - Bakar, K. Shuvo; Kokic, Philip; Jin, Huidong
Summary Previous climate research concluded that causal influences which have contributed to changes in frost risk in south‐eastern Australia include greenhouse gas concentration, El‐Niño southern oscillation and other effects. Some of the climatic indices representing these effects have spatiotemporal misalignment and may have a spatially and temporally varying effect on observed data. Other indices are constructed from grid‐referenced physical models, which creates a point‐to‐area problem. To address these issues we use a spatiodynamic model, which comprises a blending of spatially varying and temporally dynamic parameters. For the data that we examine the model proposed performs well in out‐of‐sample validation compared with a spatiotemporal model.